Epistemology of Islamic Law in The Book Al-Luma’: The Thoughts of Abu Ishaq Ibrahim Al-Shirazi - Mahmudin Mahmudin; Muhammad Sholah Ulayya; Muhammad Hamid Muhammad Bahamisy (Ad-dawl : Jurnal Islamic Studies, 2025)
This study aims to examine the epistemology of Islamic law in the book Al-Luma’ fi Ushul al-Fiqh by Abu Ishaq Ibrahim al-Syirazi, a prominent Shafi‘i scholar of the 5th century AH. The study focuses on how al-Syirazi formulates the principles of ushul fiqh, his method of ijtihad, and the rational-theological (kalamiyah) mindset that forms the basis of Islamic law. The method used is qualitative with a library research approach. The primary source of this research is the book Al-Luma’ fi Ushul al-Fiqh, while secondary sources include various fiqh books, classical and contemporary literature, and relevant scientific studies. The results show that al-Syirazi’s thought in Al-Luma’ represents the epistemological pattern of Islamic law of the mutakallimin school, which emphasizes a rational and argumentative approach. He places dalil syar‘i as the main foundation in law formation but still allows the role of reason through qiyas, urf, and istihsan in certain contexts. The comparative method used by al-Syirazi in analyzing scholars’ opinions demonstrates his intellectual breadth and freedom in bridging texts and reality. This study concludes that Al-Luma’ is not only a monumental work in the discipline of ushul fiqh but also underscores the importance of integrating nash, reason, and social reality as the foundation of a dynamic and contextual epistemology of Islamic law.